INTEGRATED AVO, ELASTIC SEISMIC INVERSION AND PETROPHYSICAL ANALYSIS FOR RESERVOIR CHARACTERIZATION: A CASE STUDY OF GAS FIELD, SOUTH SUMATERA BASIN - Abdul Haris; Ressy Sandrina; Agus Riyanto (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
Integrated Amplitude Versus Offset ( AVO), elastic seismic inversion and petrophysical analysis have been successfully applied to estimate the elastic parameters of the reservoir for a case study of the gas field in south Sumatera basin. This paper aims to have better understanding the petrophysical properties of the reservoir. The petrophysical analysis was carried out by performing routine formation evaluation that includes calculation of shale volume, porosity, and water saturation of basic well log data. Sensitivity analysis was conducted to evaluate the sensitivity parameters of the log for changing in lithology, porosity, and fluid content in the reservoir. For completing the availability of elastic parameter from well log data, shear wave logs were derived from Castagnaâ€™s mudrock line relationship. Further, P-impedance, S-impedance, VpVs ratio, LambdaRho (Î»Ï), MuRho (Î¼Ï) and density(Ï) were then calculated through a Lambda-Mu-Rho (LMR) transformation. Prior to performing AVO analysis and elastic seismic inversion, super gather technique was applied to improve the reliability of pre-stack seismic data. Elastic seismic inversion was carried out to extract the lateral elastic properties to capture lithology and fluid changes in the reservoir. In addition, AVO analysis of pre-stacked data was applied to identify hydrocarbon-bearing sandstone at target zone. The petrophysical analysis shows that porosity versus density crossplot is able to distinguish sand-shale based on 34% shale volume cutoff, while LMR crossplot is able to delineate hydrocarbon zone at water saturation value under 65%. The predicted lateral elastic parameter shows slightly higher value compare to overlying layer.